Conflicting measures of poverty and inadequate saving by the poor: The role of status-driven utility function - Sugata Marjit (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
In the presence of inequality a status-driven utility function reconciles the conflict between income-based and nutrition-based measures of poverty. Moreover, it can explain why the poor tend to save less, an established empirical fact in the developing countries. The result is independent of the assumption of imperfect capital market. The paper attempts to integrate various strands of literature on status effects.
Keywords: D63; D91; D11; I3; 330; inequality; inter-temporal consumer choice; utility; poverty; Einkommensverteilung; Armut; Sparen; Nutzenfunktion; Zeitpräferenz